(untitled) (Journal of Medical & Health Sciences Review, 2025)
Migraine is a disabling neurological condition, which must undergo fast and prolonged therapeutic management but this is often hampered by low bioavailability, first-pass degradation and gastrointestinal upheaval during the migraine episodes with the conventional method of administration in oral form as the antimigraine agents. Tryptans (zolmitryptan and frovatriptan) are commonly employed in the treatment of acute migraine but these pharmacokinetic shortcomings diminish their efficacy. Transdermal drug delivery system (TDDS) has been a new way of offering an option because it evades hepatic metabolism, leads to better systemic absorption and offers a control of drug release. This is a critical review of transdermal strategies that are worked out to deliver zolmitriptan and frovatriptan, including formulation design, drug release, skin permeability, and pharmacodynamics. Recently, it has been shown that zolmitryptan has been tested exhaustively on the basis of sophisticated nano-vesicular systems especially niosomal transdermal patches, which is based on the application of surfactants and cholesterol to augment drug encapsulation, lipid fluidization, and transdermal incursion. Such systems have biphasic release profiles, enhanced bioavailability as well as high modulation of migraine-related biomarkers in preclinical models, which show greater therapeutic potential. Transdermal preparations of frovatriptan on the other hand have mainly been concerned with standard polymeric matrix patches that are usually based on hydrophilic and hydrophobic polymers. Even though these systems are predictable and sustained drug release systems, they show poor skin permeation, and no complete in vivo pharmacodynamics and mechanistic assessment are shown. In general, comparative analysis indicates that nano-vesicular transdermal delivery systems have certain unique benefits to conventional polymeric patches in attaining quick onset of action, better skin penetration and better treatment effect of migraine. The results show that there are important gaps in the existing research on the use of frovatriptan transdermal and indicate that new carrier-based formulations and carefully designed clinical trials are needed to maximize transdermal antimigraine products.